2018
DOI: 10.3390/brainsci8100183
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Discrimination Reduces School Performance of African American Youth: Role of Gender

Abstract: Background: Gender may alter African Americans’ vulnerability to discrimination. The type of outcomes that follow exposure to discrimination may also be gender-specific. Although teacher discrimination is known to deteriorate school performance, it is yet unknown whether male and female African American youth differ in the effect of teacher discrimination on school performance. Objective: This cross-sectional study explored the moderating role of gender on the effect of teacher discrimination on school perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 119 publications
0
36
0
Order By: Relevance
“…African American adolescents receive smaller academic benefits from their parental education than their white counterparts [61,62]. In another study, MDRs were found for inhibitory control [63], impulsivity [19], aggression [4], school performance [64], depression [29], and anxiety [5].…”
Section: Discussionmentioning
confidence: 96%
“…African American adolescents receive smaller academic benefits from their parental education than their white counterparts [61,62]. In another study, MDRs were found for inhibitory control [63], impulsivity [19], aggression [4], school performance [64], depression [29], and anxiety [5].…”
Section: Discussionmentioning
confidence: 96%
“…We have previously argued that MDRs may be due to racism and discrimination in the US education system and labor market. As a result of racism, segregation, and social stratification, schools have fewer resources in the areas where ethnic minorities receive an education [29,59]. Another mechanism of the MDRs is the US labor market.…”
Section: Discussionmentioning
confidence: 99%
“…Blacks are more likely to gain their education in an inner-city school, which are low in resources. Black children and youth commonly experience discrimination [29,30]. Such discrimination increases the risk of problems across domains [24,25,31].…”
Section: Introductionmentioning
confidence: 99%
“…That means, some of the processes involved in racism may differ for males and females. For instance, discrimination by the education system [ 94 ], labor market [ 95 , 96 , 97 , 98 , 99 ], police, and correctional setting [ 100 , 101 , 102 ] may be worse for males than females. These may explain why experience and vulnerability to discrimination is worse for African American males than females [ 40 ], why high SES increases vulnerability to discrimination [ 103 ], why education attainment protects female but not male African Americans [ 18 ], and why high SES African American men and boys but not women and girls are more depressed [ 42 , 83 , 104 , 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%